“THE LAW OF THE EARTH IN OPPOSITION TO THE ASPHALT” POPULAR RELIGIOSITY, HISTORICAL CONTINUITIES AND RURAL MENTALITIES BETWEEN THE VICTORY POPULATORS 1957-1990 - Garín Abarzúa, Eduardo Marco (Revista de Historia Social y de las Mentalidades, 2024)
From social history and culture history, our interest is focused on the research of the popular religious itinerary from La Victoria settler during on 1980 decade, from its agrarian conception, in other words, peasant and indigenous traditions. Our hypothesis recognizes lines of identity continuity that qualify the eminently urban condition with which the bibliography on the movement of Chilean settlers (“pobladores”) has dealt with a privileged sear.